Hypoxia and Acidification, Individually and in Combination, Disrupt Herbivory and Reduce Survivorship of the Gastropod, Lacuna vincta - Young, Craig S.; Gobler, Christopher J. (Frontiers in Marine Science, 2020)
Acidification and deoxygenation are two consequences of climate change that also co-occur in eutrophied coastal zones and can have deleterious effects on marine life. While the effects of hypoxia on marine herbivores have been well-studied, how ocean acidification combined with hypoxia affects herbivory is poorly understood. This study examined how herbivory and survival by the gastropod Lacuna vincta grazing on the macroalgae Ulva rigida was influenced by hypoxia and ocean acidification, alone and in combination, with and without food limitation. Experiments exposed L. vincta to a range of environmentally realistic dissolved oxygen (0.7 – 8 mg L-1) and pH (7.3 – 8.0 total scale) conditions for 3 – 72 h, with and without a starvation period and quantified herbivory and survival. While acidified conditions (pH < 7.4) reduced herbivory when combined with food limitation, low oxygen conditions (< 4 mg L-1) reduced herbivory and survival regardless of food supply. When L. vincta were starved and grazed in acidified and hypoxic conditions, respectively, herbivory was additively and synergistically reduced, respectively, with low oxygen having a more inhibitory effect than low pH. Shorter exposure times (9, 6, and 3 h) were required to reduce grazing at lower DO levels ( 2.4, 1.6, and 0.7 mg L-1, respectively). Herbivory ceased entirely following a three-hour exposure to DO of 0.7 mg L-1 suggesting that episodes of diurnal hypoxia disrupt grazing by these gastropods. The suppression of herbivory in response to acidified and hypoxic conditions could create a positive feedback loop that promotes ‘green tides’ whereby reduced grazing facilitates the overgrowth of macroalgae that cause nocturnal acidification and hypoxia, further disrupting herbivory and promoting the growth of macroalgae. Such feedback loops could have broad implications for estuarine ecosystems where L. vincta is a dominant macroalgal grazer and will intensify as climate change accelerates.